2016
DOI: 10.1021/acsmedchemlett.6b00066
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Substituted 1H-Pyrazolo[3,4-b]pyridine Derivatives as Potent and Selective FGFR Kinase Inhibitors

Abstract: Fibroblast growth factor receptors (FGFRs) are important targets for cancer therapy. Herein, we describe the design, synthesis, and biological evaluation of a novel series of 1H-pyrazolo [3,4-b]pyridine derivatives as potent and selective FGFR kinase inhibitors. On the basis of its excellent in vitro potency and favorable pharmacokinetic properties, compound 7n was selected for in vivo evaluation and showed significant antitumor activity in a FGFR1-driven H1581 xenograft model. These results indicated that 7n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…ChemMedChem 2018ChemMedChem , 13,1490ChemMedChem -1507 www.chemmedchem.org particular, Zhao et al described ac lass of 1H-pyrazolo [3,4b]pyridine derivatives as potent and selective FGFRs inhibitors using the same strategy. [39] Notably,s ubstitution from the 1Hindazole to 1H-pyrazolo [3,4-b]pyridine resulted in as ignificant increasei ne nzymatic potency, suggestingt hat, in some cases, indazole can be used as building block for preparation of more potent compounds. In this study,c ompound 15 was documentedt oh ave many outstanding in vitro and in vivo biological properties.…”
Section: Blockade Of Fgfrsmentioning
confidence: 99%
“…ChemMedChem 2018ChemMedChem , 13,1490ChemMedChem -1507 www.chemmedchem.org particular, Zhao et al described ac lass of 1H-pyrazolo [3,4b]pyridine derivatives as potent and selective FGFRs inhibitors using the same strategy. [39] Notably,s ubstitution from the 1Hindazole to 1H-pyrazolo [3,4-b]pyridine resulted in as ignificant increasei ne nzymatic potency, suggestingt hat, in some cases, indazole can be used as building block for preparation of more potent compounds. In this study,c ompound 15 was documentedt oh ave many outstanding in vitro and in vivo biological properties.…”
Section: Blockade Of Fgfrsmentioning
confidence: 99%
“…Among the N ‐heterocycles, the fused pyrazolo‐pyridine derivatives have received considerable attention because of their broad‐spectrum of biological profiles and thus constitute a versatile synthetic building block in drug discovery. Many of these possess various pharmacological activities including FGFR kinase inhibition, [16] antiproliferative, [17] antimicrobial and anticancer, [18] hPPAR α agonist [19] and human A1 adenosine antagonist activities [20] . Therefore, the preparation of pyrazolo[3,4‐ b ]pyridine scaffolds is highly desirable for their immense biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years fused heterocyclic compounds have gained a renewed attention because of their significant biological activities, some of them Pyrido [2,1-b]quinazoline carboxamide motifs as antiplatelet activity, pyrido [2',3':3,4] pyrazolo [1, 5-a] quinazoline (VI) as anticancer and antimicrobial activity (Kumar et al, 2018b) have been reported in the literature. Pyrazolo [3, 4-b]pyridine derivative (VII) have known to possess antitumor, antiviral, antimicrobial and anti-inflammatory activities (Nagender et al, 2014;Zhao et al, 2016) (Figure 1). Previously, many reports have known for versatile one pot, three component reaction of aminopyrimidine, ketone and aldehydes leading to synthesis of diverse fused heterocyclic rings such as Pyrido [2,1-b]quinazoline by using different catalyst (Yang et al, 2013;Sagir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%